Analysis of fracture mechanism for al-Mg/SiCp composite materials - Maleque, Md. Abdul; Adebisi, Adetayo Abdulmumin; Zainal, Nur Izzati (IOP Publishing, 2017)
The present study aims to examine the fracture mechnism of silicon carbide particle (SiCp) reinforced aluminium matrix composite (AMC) material with 1 wt% addition of magnesium is fabricated using the stir casting process. The aluminium composite (Al-Mg/SiCp) is investigated for fatigue life and impact strength considering reinforcement weight fraction and influence of temperature on fracture toughness. The fabricated composite was tested using fatigue testing machine and charpy impact tester. Fractographic observations were evaluated with the scanning electron microscopy (SEM) on the fracture surface. It was found that increasing the SiCp weight fraction increased the fatigue life of the composite. Moreover, the 20 wt% SiCp Al-Mg composite attained the highest number of cycle and fatigue life compared to other variations. The mechanism responsible for the phenomena includes load transfer from the Al matrix alloy phase to the high strength and stiffness of the incorporated SiCp. The temperature variation influenced the impact strength of the composite and improved fracture toughness is achieved at 150 °C. It can be concluded from this study that reinforcement weight fraction and temperature affects the fracture behavior of the composites.